Wyzwania globalizacji w XXI w. – wykorzystanie strategii wierzchołka góry lodowej, efektu motyla i inteligencji wielorakiej w tworzeniu nowego modelu uczenia się - Haller-Hayon, Orit (Studia Edukacyjne, 2018)
Each student has their own individuality and special interests. One of the greatest challenges facing contemporary teachers is how to fascinate and link the students to the learning, to cause them to get excited and feel satisfaction. However, is it possible to attach different students with a diversity of abilities, dissimilar knowledge and different interests, to the same subject? Or is it a dream that cannot be fulfilled? The current article will introduce a new learning model, by using the ‘iceberg learning model’, understanding the influence of the ‘butterfly effect’ and the connection to the special ‘multiple intelligences’ of each student. Instead of seeing the subject of learning as a collection of facts, the concept of the iceberg sees the subject as a vast world full of information connected to endless forms related to the students’ areas of life. Therefore, the Iceberg learning method allows each student to be linked to the learning topic according to their own abilities, interests and desires; by using their unique strengths and utilizing their individual substantial intelligences.